ENHANCEMENT OF THE DESIGNER PERFORMANCE IN OFFICE INTERIOR DESIGN - Karaaslan, Tuba; Yazıcıoğlu, Deniz Ayşe (Advances in Social Sciences Research Journal, 2015)
It is also a reality in the literature that the developing and changing conditions have become inevitable for being considered in the area of interior space design and application and being directed towards restructuring works in this regard. In this approach, one of the key concepts is “performance-based design”. It is also being tried to develop models intended for determination of factors affecting the performance of a specific actor, within a certain period, among the works related to the performance. One of the most important actors for interior space design is the designer. In Kleeman’s opinion, designer’s success primarily depends on his/her capability to fulfill accurately and completely the evaluations intended for recognizing the user at the preliminary stage. Because, the success of interior space design, is measured through to what extent it meets the user’s desires and needs. In this context, the purpose of the study has been decided as reviewing the documents used during determination of the user’s desires and needs at the preliminary stage and recommending necessary revisions in order to acquire complete, accurate data. The scope of the study has been limited to only office interior space design projects for the purpose of reaching detailed results. In line with this scope and objective defined, literature and practical application resources have been investigated as the methodology at the first stage in order to determine the documents utilized towards recognition of the user at office design. Afterwards, the entire documents obtained have been examined by comparing in a systematic manner and deficiencies of these documents have been set forth. And at the last stage, some suggestions have been made for elimination of these deficiencies.